The Relationship Between Emotional Intelligence And Effective Leadership Among Academic Heads In Higher Learning Private Educational Institutions In Malacca - Cheah, Yeh Ying (2005)
The focus of thi study was to determine the whether or not the emotional intelligence of academic heads was related to the lecturer's perceptions of the academic head's effectiveness as a leader.